Moving from maternal death review to surveillance and response: A paradigm shift - Amrita Kansal; Suneela Garg; Malvika Sharma (Wolters Kluwer Medknow Publications, 2018)
In the era of the sustainable development goals, India is committed to reduce its maternal mortality ratio to less than 70 per one lakh live births by 2030. An important strategy that was adopted in the Reproductive and Child Health Programme in 2010 was maternal death review. Analysis of the progress so far has brought to light certain gaps which have prompted the paradigm shift toward Maternal Death Surveillance and Response (MDSR), which focuses on taking action on information obtained from every maternal death so as to prevent further maternal deaths. The new guidelines on MDSR were released by the Ministry of Health and Family Welfare in 2017.